The value of microparticles in detecting acute rejection episodes after liver transplantation. (2nd January 2018) - Morgul, Mehmet Haluk; Splith, Katrin; Leonhardt, Christoph; Raschzok, Nathanael; Reutzel-Selke, Anja; Schmuck, Rosa Bianca; Andreou, Andreas; Atanasov, Georgi; Benzing, Christian; Krenzien, Felix; Hau, Hans-Michael; Felgendreff, Philipp; et al.
Abstract: Context: Non-invasive markers for diagnosis of acute rejection (AR) following liver transplantation have not been developed, yet. Objective: We analyzed the correlation of plasma microparticle levels (MP) with AR. Materials and Methods: MP (CD4, CD8, CD25, CD31, MHC) of 11 AR patients and 11 controls were analyzed within the first week after transplantation. Results: CD4, CD8 and CD31 positive MP were higher in the AR, whereas overall MP count, CD25 and MHCI positive MP proportions did not differ between both groups. Discussion and Conclusion: MP dynamics within the first period of transplantation could help to clarify on-going mechanisms of immunomodulation.